The Effect of Obesity on Brain Diffusion Alteration in Patients with Obstructive Sleep Apnea - Rukiye Kilicarslan; Alpay Alkan; Rasul Sharifov; Muhammed Emin Akkoyunlu; Ayse Aralasmak; Abdulkadir Kocer; Levent Kart (The Scientific World Journal)
Purpose. We investigated diffusion alterations in specific regions of the brain in morbid obese, obese, and nonobese OSA patients and searched whether there is a correlation between BMI and ADC values. Materials and Methods. DWIs of 65 patients with OSA were evaluated. The patients were classified according to BMI as morbid obese (n=16), obese (n=27), and nonobese (control, n=22) groups. ADC measurements were performed from 24 different regions of the brain in each patient. The relationship of BMI with ADC values was searched. Results. The ADC values in hypothalamus, insular cortex, parietal cortex, caudate nucleus, frontal white matter, and posterior limb of internal capsule were all increased in obese patients (n=43) compared to control group. The ADC values of midbrain, hypothalamus, orbitofrontal cortex, and parietal cortex were significantly increased in morbid obese compared to obese patients. In obese patients, the degree of BMI was positively correlated with ADC values of orbitofrontal cortex, parietal cortex, and hypothalamus. Conclusion. We observed increasing brain vasogenic edema with increasing BMI, suggesting that the main reason of brain diffusion alteration in patients with OSA could be obesity related.